Tinjauan Yuridis Pertanggungjawaban Hukum Kartu Kredit Pemerintah Di Indonesia - Pratama, Shandy Aditya; Salam, Abdul (Jurnal Hukum & Pembangunan, 2019)
Government credit cards are new products whose applications are currently being piloted by the Directorate General of State Treasury to a number of work units and government institutions. This credit card is intended for government employees as a means of payment in order to use inventory money. Based on the Regulation of the Director General of Treasury No. PER-17/PB/2017, sanctions imposed on misuse of government credit cards are only by giving a warning letter and revocation of the credit card. By examining the elements of legal liability, this paper shows what sanctions can actually be imposed for misuse of government credit cards. This study is carried out by paying attention to the elements of legal accountability from the perspective of civil law, criminal law, and state administrative law. This paper found that a government credit card is in principle the same as a corporate credit card, but the specific thing is that in its accountability. With regard to government cards, there is administrative legal liability.